2020
DOI: 10.1001/jamanetworkopen.2020.0038
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Long-term Mortality and Patterns of End-of-Life Care Among Medicare Sepsis Survivors Discharged to Home Health Care

Abstract: IMPORTANCE Despite a growing recognition of the increased mortality risk among sepsis survivors, little is known about the patterns of end-of-life care among this population. OBJECTIVE To describe patterns of end-of-life care among a national sample of sepsis survivors and identify factors associated with long-term mortality risk and hospice use. DESIGN, SETTING, AND PARTICIPANTS This cohort study assessed sepsis survivors who were Medicare fee-for-service beneficiaries discharged to home health care using nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 52 publications
1
38
0
1
Order By: Relevance
“…Potential explanations for the low COVID-19 readmission rate include increased use of acute rehabilitation, given the relationship between acute rehabilitation and improved outcomes among sepsis survivors ( 30 ); increased use of home health services, given data suggesting that early and intense home health care is associated with fewer rehospitalizations ( 31 ); unprecedented support at home in the setting of the pandemic; and a new phenotype of sepsis survivors who may have fewer subsequent infections ( 29 ). However, given the rate of persistent lymphopenia observed and known increased risk for 1-year mortality after sepsis ( 32 , 33 ), studies designed to examine the long-term health of COVID-19 survivors are needed. Of note, COVID-19 survivorship and disposition outcomes may be biased because of challenges with post–acute care placement due to infection control concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Potential explanations for the low COVID-19 readmission rate include increased use of acute rehabilitation, given the relationship between acute rehabilitation and improved outcomes among sepsis survivors ( 30 ); increased use of home health services, given data suggesting that early and intense home health care is associated with fewer rehospitalizations ( 31 ); unprecedented support at home in the setting of the pandemic; and a new phenotype of sepsis survivors who may have fewer subsequent infections ( 29 ). However, given the rate of persistent lymphopenia observed and known increased risk for 1-year mortality after sepsis ( 32 , 33 ), studies designed to examine the long-term health of COVID-19 survivors are needed. Of note, COVID-19 survivorship and disposition outcomes may be biased because of challenges with post–acute care placement due to infection control concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Readmissions after discharge are common (21% within 30 days) [ 11 ], and sepsis survivors have increased post-discharge mortality [ 12 14 ]. Post-discharge deaths have been associated with premorbid health status and hospital factors [ 15 , 16 ], but it is unclear whether these factors are modifiable, and whether hospital care can alter the post-discharge course.…”
Section: Introductionmentioning
confidence: 99%
“…Prescott, Langa ( 17 ), Yende, Kellum ( 22 ), and Courtright, Jordan ( 23 ) conducted cohort studies in septic patients. The authors had the main objective of assessing the mortality rate after one year of hospital discharge.…”
Section: The Rates Of Death Of Septic Patients After Hospital Discharmentioning
confidence: 99%
“…Yende, Kellum ( 22 ) demonstrated that in addition to the high mortality rate, survivors showed a persistent increase in the blood levels of inflammation and immunosuppression biomarkers associating these observations with worse long-term outcomes. Courtright, Jordan ( 23 ) also pointed out that 68.2% the patients who died were re-hospitalized in the last 30 days of life.…”
Section: The Rates Of Death Of Septic Patients After Hospital Discharmentioning
confidence: 99%